Ce que peut la finance publique : la Caisse des dépôts actionnaire dans l’immobilier depuis la Seconde Guerre mondiale - Raphaël Frétigny (Revue de la Régulation)
The article deals with Caisse des dépôts et consignations’ (CDC) holdings in real estate since the 1950s. The shareholder strategies of this public financial institution are characterized by a gradual increase in profitability logics, modelled on those of private financial actors. However, these developments are proving to be more complex than outright submission to financial market standards. Through methods that vary over time, CDC supports housing policies to the detriment of the rise in dividends. From a historical perspective, this case reveals how the public shareholding is not transformed by a coherent general plan or a radical submission of the public financial elites to the standards of the financial market, but rather by small, sometimes contradictory steps by public actors in reaction to the economic and political context.